Psychological Subject in News Headlines of University Websites in Indonesia: An Applied Linguistics Perspective - Pamungkas, Kasno; Mita Amalia, Rosaria; Lesmana, Ronny; Kadarisman, Ade; Rustandi, Dedi (International journal of applied linguistics & English literature, 2018)
Many researches on linguistics either traditional or functional linguistics have been conducted in both pure linguistics and applied one. Included into the applied one, this research aims to describe Psychological Subject (PS) in the news headlines of university websites in Indonesia beside the meta description that influences the reader to click the website. The method used in this research is descriptive analysis by using data from the news headlines of 5 (five) university websites in Indonesia. The results of this research show that the elements of PS in the news headlines are the name or identity of universities, the elements of university, the activities conducted in the universities, and the other parties which conduct activities in or together with the universities. These PSs become significant since they are important factors of headlines of the news which increase the accesability of the university websites. In order to improve the accessability of the university websites, the appropriate PS should be selected to fill the headlines of the news.